Mapping the implementation of carbon tax in Indonesia: Literature review and optimisation strategies - Rexipal, Dewangga; Santoso, Agnes Novita Mega Putri; Ramadhan, Ammar; Maulana, Ridho (WIM Solusi Prima, 2024)
This research aims to map out how to achieve optimisation of carbon tax implementation in Indonesia based on the framework of carbon tax implementation in developing countries. The research is conducted through a literature study, by reviewing theories and findings from other researchers related to carbon tax implementation, application, positive impacts, and negative impacts. The study highlights the importance of establishing an effective carbon tax policy to reduce emissions and combat climate change, while also considering the challenges of limited data and capacity, social impacts, and coordination between ministries. This study also discusses the current condition of carbon tax implementation in Indonesia and discusses policy recommendations for optimal implementation. The results show that the current condition implementation carbon tax in Indonesia still has many things that need to be considered so that it can be optimised. This research is expected to contribute to the literature on carbon tax implementation in Indonesia and provide considerations for the Ministry of Finance in formulating carbon tax implementation policies.